Tactic response of bacteria to zero-valent iron nanoparticles. (June 2016) - Ortega-Calvo, José-Julio; Jimenez-Sanchez, Celia; Pratarolo, Paolo; Pullin, Huw; Scott, Thomas B.; Thompson, Ian P.
Abstract: The microbial assessment of pollutant toxicity rarely includes behavioral responses. In this study, we investigated the tactic response of Pseudomonas putida G7, a representative of soil bacterium, towards engineered zero-valent iron nanoparticles (nZVIs), as a new end-point assessment of toxicity. The study integrated the characterization of size distribution and charge of nZVIs and tactic reaction response by means of inverted capillary assay and computer-assisted motion analysis of motility behavior. Iron nanoparticles (diameter ≤ 100 nm) were prepared in the absence of oxygen to prevent aggregation, and then exposed in aerobic conditions. We first demonstrate that iron nanoparticles can elicit a negative tactic response in bacteria at low but environmentally-relevant, sub-lethal concentrations (1–10 μg/L). Cells were repelled by nZVIs in the concentration gradients created inside the capillaries, and a significant increase in turning events, characteristic of negative taxis, was detected under exposure to nZVIs. These tactic responses were not detectable after sustained exposure of the nanoparticles to oxygen. This new behavioral assessment may be prospected for the design of sensitive bioassays for nanomaterial toxicity. Highlights: Bacteria show negative taxis to zero-valent iron nanoparticles. Repellence occurs at low, sub-lethal concentrations. This process reflects a toxic reaction and it is dependent on nanoparticle aging. The reaction may prove to be an effective sensitive bioassay for nanomaterials. Abstract : Bacterial tactic response to zero-valent iron nanoparticles occurs at low, sub-lethal concentrations, reflects a toxic reaction, and is strongly dependent on nanoparticle aging.